Changes in metabolism of inorganic polyphosphate in rat tissues and human cells during development and apoptosis - Lorenz, B. (2015)
Age-dependent studies show that the amount of inorganic polyphosphate in rat brain strongly increases after birth. Maximal levels were found in 12-months old animals. Thereafter, the concentration of total polyphosphate decreases to about 50%. This decrease in the concentration of total polyphosphate is due to a decrease in the amount of insoluble, long-chain polyphosphates. The amount of soluble, long-chain polyphosphates does not change significantly in the course of ageing. In rat embryos and newborns, mainly soluble polyphosphates could be detected. In rat liver, the age-dependent changes are less pronounced. The changes in polyphosphate level are accompanied by changes in exopolyphosphatase activity, which degrades the polymers to orthophosphate; highest enzyme activities were found when the polyphosphate level was low, Induction of apoptosis in the human leukemic cell line HL-60 by actinomycin D results in degradation of long polyphosphate chains. The total polyphosphate content does not change significantly in apoptotic cells.